3D printed O2 indicators. Issue 12 (29th May 2020) - Yusufu, Dilidaer; Han, Ri; Mills, Andrew
Abstract : Production of an array of O2 sensitive dots using 3D printing from the appropriate filament produced by extrusion. Abstract : A polymer filament, containing an O2 -sensitive lumophore pigment, platinum(ii ) (pentafluorophenyl) porphyrin coated onto nanoparticulate silica particles, i.e. PtTFPP/SiO2, is produced and used in a filament which is then 3D printed as O2 -sensitive indicator dots (1 cm diameter, 30 μm thick) on a polyethylene terephthalate (PET) supporting film substrate. Two different filaments, prepared using the polymers, low density polyethylene (LDPE) and polylactic acid (PLA), respectively, are used to produce 3D printed PtTFPP/SiO2 /LDPE and PtTFPP/SiO2 /PLA O2 -sensitive indicator dots, with dynamic ranges of 0–30% and 0–400% O2, respectively. The O2 response characteristics of these two, very different, indicator dots, such as sensitivity, response time and temperature sensitivity, are measured and compared with those of a commercial O2 indicator, FOSPOR (OceanInsight) and other commercial O2 indicators. The potential of this method for mass manufacture of O2 indicator dots and the likelihood that it can be extended to produce other optical indicators, such as those for ammonia or CO2, are discussed briefly.